Predicting Stock Prices Using Data Mining Technique - Thuy, Nguyen Thi Thu; Thi-Lich, Nghiem (INTI International University, 2023)
The stock market, for a long time, has been known as a complicated yet captivating system. It is a mainstream investment platform for both beginners and financially savvy people to grow and hold their assets. While it remains a good way to earn profit, the stock market is often considered as one of the risky approaches, mostly due to the nature of the field, and an enormous number of various factors that not often welcome the naïve investors. Therefore, the demand for using a tool that can support us on an overall view of the market trends, facilitating the financial analysis and strategies to identify the optimal time to purchase stocks and the actual stocks to purchase has risen for many years recently. In this study, we focus on using data mining techniques that can support investors in predicting the stock price with existing data from previous phrases. Given data is taken from Yahoo Finance within the 7-year period from 2015-2022. This data will be used to train the algorithms, then we can decide which one is the most suitable for the data mining tools to give the best suggestions for investors.